Regional outbreak of multidrug-resistant Klebsiella pneumoniae carbapenemase–producing Pseudomonas Aeruginosa. (1st October 2021) - Tadese, Bekana K.; Nutt, Anna; Chaudhary, Ifrah; Offiong, Charlene; Darkoh, Charles
Abstract: Klebsiella pneumoniae carbapenemase-producing P. aeruginosa ( KPC-CRPA) are rare in the United States. An outbreak of KPC-CRPA was investigated in Texas using molecular and epidemiologic methods and 17 cases of KPC-CRPA were identified. The isolates were genetically related and harbored the emerging P. aeruginosa multilocus sequence type 235, the first in the United States.